Virulence spectrum of South American isolates of Colletotrichum gloeosporioides on selected Stylosanthes guianensis genotypes - Kelemu, Segenet; Badel, JL; Moreno, CX (Scientific Societies, 1996)
Anthracnose, caused by Colletotrichum gloeosporioides, is the most important and widespread disease of Stylosanthes, a diverse tropical and subtropical forage legume naturally distributed in Central and South America. Although South American isolates of C. gloeosporioides are known to be variable in pathogenicity, no suitable differential host lines have been identified to fully characterize them. This study takes advantage of new S. guianensis inbred lines, cultivars, and accessions to describe the pathogenicity of South American isolates of C. gloeosporioides and to select potentially useful differentials. Seedlings of 23 S. guianensis genotypes were inoculated with 45 isolates from various regions of South America. Virulence patterns were used to select 12 differentials and determine 23 pathotypes in C. gloeosporioides. In contrast, the same isolates were grouped into nine pathotypes with the four Australian differentials currently in use.